The relationship between psychological distress and impairment of disease-specific quality-of-life compared between liquid sclerocompression therapy and invasive treatments in patients with superficial venous disease during a one-year follow-up. (October 2021) - Krasznai, Attila G; Catarinella, Fabio S; Houtermans-Auckel, Janine; Nieman, FHM; Wittens, IAJ; Mooij, MC; Wittens, Cees HA
Introduction: Superficial venous disease (SVD) is a very common disease and much research has been done towards finding the ideal treatment and discovering the pathophysiology of SVD. Not much is known about the psychological burden of SVD. Current guidelines and scientific publications tend to focus on clinical and physiological aspects of SVD. The aim of this study was to relate the changes in Quality-of-Life (QoL) after SVD treatment to possible changes in psychological distress (PD). Methods: A prospective cohort was set up with the assistance of 5 specialized vein clinics in the Netherlands. Inclusion criteria were: 18 years of age or older, fluent in Dutch language, C1 to C6 (CEAP) class intended to be primary treated with either endovenous laser(LA), radiofrequency ablation (RFA) and phlebectomy(PHL) or sclerocompression therapy alone (SCT). Patients were divided in two groups: 1. C1-C3 patients treated by SCT 2. C1-C6 patients treated invasively (LA, RFA and PHL) Outcomes were a disease specific QoL questionnaire (CIVIQ-20) and a questionnaire to assess PD (Hospital Anxiety and Depression Scales (HADS)). This study was approved by the local institutional review board, following the principles outlines in the Declaration to Helsinki. This trial was registered in the ISRCTN registry with study ID ISRCTN12085308 Results: 442 patients were included in the study and completed the T0 measurements. Mean age of these patients is 54.4 years (s.d. 12.9, 17-90). Number of females: 349 (79.0%), of males: 93 (21.0%). The mean baseline (T-0) HADS depression (0-3) scale scores is 2.54 (s.d. 0.51, n = 412). The mean one-year difference between T-12 HADS depression (0-3) scale scores and baseline T-0 scores is +0.06. The mean baseline (T-0) HADS anxiety (0-3) scale scores is 2.19 (s.d. 0.5, n = 283). The mean one-year difference between T-12 HADS anxiety (0-3) scale scores and baseline T-0 scores is +0.06. Controlled for baseline scores, gender, age, weight and length(BMI), patients in group 2 (receiving invasive treatment) show significantly higher one-year improvement in the QoL of their psychological state of mind than patients in group 1 (receiving SCT and having C1, 2, 3) (beta 0.158 p = 0.002). Conclusions: The significant improvement in psychological, QoL and clinical scores that we observe after successful invasive treatment compared to no significant improvement after SCT and the lack of psychological distress in patients with "simple" SVD indicates that SCT is mainly performed for cosmetic reasons. One could thus argue that reimbursement of SCT as a stand-alone medical treatment is debatable.